2016
DOI: 10.1038/srep28242
|View full text |Cite
|
Sign up to set email alerts
|

An excellent navigation system and experience in craniomaxillofacial navigation surgery: a double-center study

Abstract: Numerous problems regarding craniomaxillofacial navigation surgery are not well understood. In this study, we performed a double-center clinical study to quantitatively evaluate the characteristics of our navigation system and experience in craniomaxillofacial navigation surgery. Fifty-six patients with craniomaxillofacial disease were included and randomly divided into experimental (using our AccuNavi-A system) and control (using Strker system) groups to compare the surgical effects. The results revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Large bone grafts to replace portions of medial and lateral orbital floor and walls benefit from the positional referencing provided by navigation when positioning grafts, in an effort to avoid postoperative enophthalmos. Although navigational technology requires extra time, the increase in operative duration is an offset by the accuracy of the reconstruction, as an improperly positioned reconstruction can have both functional consequences as well as require revisionary procedures …”
Section: Maxillary Reconstructionmentioning
confidence: 99%
“…Large bone grafts to replace portions of medial and lateral orbital floor and walls benefit from the positional referencing provided by navigation when positioning grafts, in an effort to avoid postoperative enophthalmos. Although navigational technology requires extra time, the increase in operative duration is an offset by the accuracy of the reconstruction, as an improperly positioned reconstruction can have both functional consequences as well as require revisionary procedures …”
Section: Maxillary Reconstructionmentioning
confidence: 99%
“…proposed a protocol for assessing the surgical simulation, guide positioning, intraoperative navigation, and outcome validation provided by computer-assisted surgery systems3839. The 3D virtual surgery combined with navigation was proposed and suggested that simulation-guided navigation makes accurate postoperative outcomes possible for maxillary repositioning in orthognathic surgery404142434445. However, the improvement from the 3D technique over the conventional method should be quantitated.…”
mentioning
confidence: 99%
“…The use of the navigation system during surgical procedures may be helpful when applied to patients with complicated disease conditions. [9] There are some vital structures around the TMJ such as the middle ear, middle cranial fossa, vessels, and nerves. [10] There is a high risk of damaging these vital structures under subjective visual assessment in open surgery of TMJ.…”
Section: Discussionmentioning
confidence: 99%